Evaluation of the Effectiveness of the National Vision Screening Program in School-Age Children - Mehtap Savar Çağlayan; Betül Dertsiz Kozan (Trends in Surgical Sciences, 2025)
Objective: Visual defects are common in school-age children and are one of the factors that negatively affect school success. The aim is to evaluate the ophthalmic findings, the effectiveness of the vision screening program in school-age children who are referred to an Ophthalmologist because they have problems as a result of the vision screening program implemented by school counselors.Methods: Our study included demographic characteristics of the patients who applied to the Ophthalmology clinic between January 2023 and December 2024 due to the guidance of the guidance counselor at school, best corrected visual acuity with Snellen chart, dilated and nondilated autorefractometer, eye movements, biomicroscopy and fundus examination, color blindness and additional findings. The family was asked whether the child had been taken to an ophthalmologist before and their knowledge of the vision screening program.Results: 74 cases were included in our study. 38 (51.4%) of the cases were girls and 36 (48.6%) were boys. The average age was 6.8±1.6 (4-11) years. 36 (48.6%) of the cases were emmetropic, 20 (27.0%) were myopic, 4 (5.4%) were hyperopic, 10 (13.5%) were mixed astigmatic and 4 (5.4%) were astigmatic. Amblyopia was detected in 12 (16.2%) of the cases, exotropia was detected in 2 (2.7%), and color blindness was detected in 1 (1.3%). None of the families stated that they had ever taken their children to an ophthalmologist before. About the vision screening program, 20 (27.0%) families stated that they knew that it was carried out in schools. None of the families had any information about the vision screening program performed at the family doctor during the preschool period.Conclusion: Implementation of screening vision programs at an early age is important in detecting preventable vision loss. Vision screening before primary school age may be effective in reducing the risk of amblyopia. Providing families with information about the vision screening program may reduce the risk of amblyopia.